GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 570158111 species occurrences available in GBIF matching the query: All data. The dataset includes 570158111 records from 13220 constituent datasets: 42 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Passeridae. 5860 records from Loopkevers Grensmaas - Carabid beetles near the river Meuse in Flanders, Belgium. 66081 records from HUFU - Herbarium Uberlandense. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 49 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 1. 18 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 15474 records from Herbarium Erlangense. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 85 records from Birdrace-Die_Paradiesvögel-Herford. 21 records from LBV-Kindergruppen Markt Tussenhausen. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 113 records from Tornoer Teich. 9879 records from Bibliographic records of Angola mammals. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 11 records from Microzooplankton abundance and biomass at station TT043_28-1. 30 records from Phytoplankton abundance in surface water in 2001, Ancon, Peru. 10 records from Phytoplankton abundance at station Sechin_2003-08-06_2, Casma, Peru. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-9. 40 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733. 260 records from Range table from ostracoda in ODP Hole 144-873B. 761 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 40472 records from MEXU/Colección de Briofitas. 196 records from Foraminifera abundance of Hole 33-317A. 102 records from Range table from benthic foraminifers in ODP Hole 139-858A. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 44 records from Solanum_baretiae. 8 records from Microzooplankton abundance and biomass at station NBP97-03-16-1. 229 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1756-5. 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 4 records from Nannofossil abundance of Hole 10-89. 672 records from Colección de Entomología - Curculionidae. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 1603 records from Fossil (MNHM-FO). 2072 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 14590 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 15 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 6 records from Microzooplankton abundance and biomass at station NBP97-08-08-1. 16 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 74-527. 27 records from Smear slide analysis on sediment core GeoB4212-2. 51 records from Coccolith counts of multinet M32/5_MSN971. 2 records from Nannofossil abundance of Hole 10-87. 53 records from Squid collection from 1995/96 V4 BROKE. 6414 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. ECOSUR_SNIB. 6050 records from CUBA: Herbario de la Academia de Ciencias, La Habana, Cuba: HAC-Pteridophyta. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 17400 records from Sam Mitchel Herbarium of Fungi (Denver Botanic Gardens). 284 records from Botanical collection of the National Museum. 42 records from Ostracoda abundance of Hole 48-406. 129 records from Nannofossil abundance of Hole 29-284. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 13 records from Benthic macrofauna abundance of sediment core 12930-073. 19885 records from Natural History Museum Rotterdam (NL) - Chordata collection. 495 records from Life Science National Tsing Hua University. 2 records from Nannofossil abundance of Hole 1-1. 48 records from Abundance of phytoplankton in surface water during THALASSA campaign PROSOPE. 815 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 1221 records from NBM Unionoids. 1083 records from Percentages of planktonic foraminifera species in sediment core V29-144. 235 records from Klutensee. 40 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200500. 4 records from Description of a new species of Labeo (Teleostei: Cyprinidae) from the lower Congo River.. 1974 records from Range table from planktonic foraminifers in ODP Hole 160-967E. 14 records from (Tab. 7) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 43-384, J-Anomaly Ridge, Grand Banks off Nefoundland. 33 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Stylops (BNHS) â 1930-1971. 2702 records from (Appendix B) Abundance of benthic foraminifera in sediment cores GIK17964-3 and GIK17964-2. 2288 records from (Table 2) Distribution of microfossils in the Barrow Group of ODP Site 122-763. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 26753 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 11459 records from Herbario de la Universidad de Sevilla, SEV-Historico. 9319 records from Itami City Museum of Insects. 2115 records from Planktic foraminifera assemblage of sediment core ELT49.021-PC. 1036 records from Benthic foraminifera distribution of sediment core ASV1200. 133 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 170 records from (Fig. 3) Relative abundance of Emiliania huxleyi in sediment core MD99-2343. 539 records from Bay of Puck dataset (EurOBIS). 1513 records from M. Gollop Collection. 21593 records from CNCR/Colección Nacional de Crustaceos. 742 records from (Appendix A) Relative abundances of smaller size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 213 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 58 records from Occurrence of mammalia relicts at site Sandalja II. 12 records from Occurrence of mammalia relicts at site Dolni Vestonice. 1047 records from Planktic foraminifera abundance of Hole 21-206. 206 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 150 records from Isotope age and relative abundance of planktonic foraminifera in Core Vulk-34-90, Sea of Okhotsk. 373 records from Otter survey of Ireland 2004 & 2005. 201 records from Planktic foraminifera abundance of Hole 4-31. 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 1 records from On centipedes (Chilopoda) of Albania, 2. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 148 records from Total foraminifera counts from multinet SO119_MSN1278. 5 records from Trap data GBZ4, 696 m. 102 records from Planktic foraminifera abundance of Hole 67-498A. 1 records from Dinoflagellate abundance of Hole 38-343. 805 records from Relativ abundances of live fauna of benthic foraminifera in surface sediments (Table C2.1). 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 1 records from Abundance of benthos infauna at station GIK23038-1. 164 records from Terrestrial molluscs at the Natural Park of the Serralada Litoral (Barcelona, Spain). 73069 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 169 records from Planktic foraminifera counts at CTD station PS55/051. 3 records from Nannofossil abundance of Hole 1-7. 859 records from Royal Horticultural Society - RHS berberis sawfly (Arge berberidis) monitoring. 2197 records from Benthic foraminifers of sediment core Svanic90_9004. 25592 records from Herbarium Amazonense. 470 records from Phytoplankton abundance during Lev Titov cruise LT90/5. 9 records from Numbers and dry weight of main macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 3). 6 records from Two new dolichoderine ant genera from Madagascar: Aptinoma gen. n. and Ravavy gen. n. (Hymenoptera: Formicidae).. 3 records from Re-description of Cultroribula berolina Weigmann, 2006 (Acari, Oribatida, Astegistidae) from Germany with a key for the European species. 63 records from Planktic foraminifera counts of sediment core RC13-154. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 48 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE218. 240 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part I. 1700 records from Nuevos registros de esponjas del Pacífico mexicano, Mar de Cortés y Archipiélago Revillagigedo. 91 records from Birdrace-Enger_am_Spektiv-Herford. 15 records from Kirchheller Heide ( Bottrop). 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 126 records from Total foraminifera counts of multinet M11/1_MSN517. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 62 records from Abundance of coccosphere-units of sediment core GIK23400-3. 6 records from Nannofossil abundance of Hole 67-494A. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 42507 records from Bird Collection of Museum and Institute of Zoology PAS. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 2275 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 254 records from BIRDRACE Thüringer Becken-Birders. 137 records from Planktic foraminifera counts at CTD station PS55/030. 9 records from Microzooplankton abundance and biomass at station TT043_11-1. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 319 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 864 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 5 records from Nannofossil abundance of Hole 29-278A. 4 records from Ostracoda abundance of Hole 32-305. 9 records from Nannofossil abundance of Hole 11-99A. 694 records from Gastropoda, scaphopoda and amphineura abundance of surface sediments of the Atlantic continental shelf off Southern Spanish Sahara, West Africa (Table 2). 458 records from PeECE I - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway, 2001. 1157 records from ISU Mammals. 1384 records from Bridel Herbar. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 511 records from Coleoptera of Swierklaniec Forest. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 7410 records from Helgeland Museum, Lepidoptera. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 98 records from Rund ums Cani. 78 records from Birdrace-Die_Laufenten-Braunschweig. 4 records from Microzooplankton abundance and biomass at station TT050_26-17. 6 records from Microzooplankton abundance and biomass at station NBP97-08-37-4. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-10-2. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 6 records from Wiese. 182 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 255 records from Planktic foraminifera counts of sediment core RC09-150. 31 records from Aktionstag Wiese am Vogelhammerkopf. 2427 records from Ibaraki Nature Museum, Mollusk collection. 368 records from Great Lakes Forestry Centre Insect Collection. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 13 records from FND "Weißer Berg" Leißling. 1023 records from (Appendix Table 1) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 2 records from (Fig. 5) Pollen analysis of the Furo do Chato core. 11 records from Microzooplankton abundance and biomass at station TT043_17-1. 11 records from Microzooplankton abundance and biomass at station TT045_4-1. 20 records from The interstitial subsoil fauna of the medium beach level at Sarso Beach, Red Sea (Table 3). 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 15 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 3709 records from Plant (MNHM-PL). 22 records from Geophagus abalios, G. dicrozoster and G. winemilleri (Perciformes: Cichlidae), three new species from Venezuela.. 702 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 1470 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 108-662A. 16604 records from Iberian Odonata distribution: data of the BOS Arthropod Collection (Univ. Oviedo, Spain). 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 20 records from Distribution of planktonic foraminifera and other biogenic components in ODP Hole 113-693A (Figure 2). 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 321 records from Nova Scotia Department of Natural Resources, Subenacadie, NS, Canada. 127133 records from Fish specimens. 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 565 records from Biodiversidad de productores primarios de lagunas costeras del norte de Yucatán, México_2. 196 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 195 records from Altenburg bei Bamberg. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MAY-1995-D4. 123 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 1460 records from Range table from benthic foraminifers in ODP Hole 151-909C. 631 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-898A. 1264 records from Hare Survey of Ireland 06/07 - Non Hare records. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 1 records from Tunicata ZMK. 36 records from Salzwiese Diekskiel. 3045 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 811 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 52181 records from ANTARCTIC PLANT DATABASE. 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 36254 records from Fish collection of National Museum of Nature and Science. 19164 records from The Gordon Alexander Orthoptera Collection. 1684 records from MfN Fish Collection, Zoology. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D4. 181 records from Occurrence of mammalia relicts at site Kemathenhöhle. 4 records from Occurrence of mammalia relicts at site Ahlen. 808 records from Range table from planktonic foraminifers in ODP Hole 154-925B. 48 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 17 records from Benthic foraminifera abundance of Hole 11-108. 169 records from Whale log - observations from ANARE voyages. 1740 records from Monitoring data from the federal state Berlin (Germany). 317 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - iSpot (2008-2010): Shieldbugs & allied species. 6943 records from DMNS Egg Collection (Arctos). 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 220 records from Total foraminifera counts of multinet SO118_MSN1253. 1358 records from Electron Micrograph Database (Australian Antarctic Data Centre). 46156 records from Zooplankton in the bay of Biscay (1995-2004 Yearly spring DEPM surveys). 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 354 records from Foraminifera distribution of sediment core KS310. 3 records from Analyses of the recent components of sediment core PS1215-2. 43 records from Vogelstimmenführung durch den Tiergarten. 19 records from Occurrence of mammalia relicts at site Gröbern. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 290333 records from AMNH Mammal Collections. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 6 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 398 records from Tsetse flies of East Africa update. 4390 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 5570 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 399 records from Colecciones Zoológicas de la Universidad de León, Colección de Poliquetos. 160757 records from Slovenian Fungal Database - Boletus informaticus. 85 records from Unterbrucker Weiher. 22 records from Occurrence of mammalia relicts at site Castlepook Cave. 68 records from Occurrence of mammalia relicts at site l´Abri du Morin. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 3324 records from Crustacea collection of the Finnish Museum of Natural History. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 156 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 218 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5. 176 records from (Appendix E) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 161-976C. 1320 records from (Table 8D) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 15-4 through 19-3. 2546 records from The atlas of butterflies in Kraków. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 1 records from Hoplophora decumana. 17 records from Hazel Dormouse in Ireland. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 128 records from Total foraminifera counts of multinet M42/3_MSN1359. 136 records from Total foraminifera counts of multinet PO247/2_MSN1380. 35 records from Planktic foraminifera of sediment core GeoB1404-3. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_832-7. 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 16 records from Nannofossil abundance of Hole 11-106B. 4702 records from Amphibian specimens. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 5 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_818-16. 240 records from Coleoptera identified from the Woolwich Manor Way site, Becton, London. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 79 records from Plasm bearing foraminifera counts of multinet M21/2_MSN628. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/061-3. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_10-CTD124. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 45 records from Nannofossil abundance of Hole 64-481A. 13960 records from Collection Trichoptera - SMF. 802 records from Biological Collection, National Institute of Oceanography, Goa, India. 66 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-5. 16 records from Phytoplankton abundance at station Sechin_2003-12-03_1, Casma, Peru. 12 records from Distribution of meiobenthos in sediment core M19_239-2 of the northeastern Atlantic (Table 1). 40 records from Coccolith counts of multinet M32/5_MSN979. 18 records from Nannofossil abundance of Hole 8-73. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 66 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 113-689. 75 records from Planktic foraminifera counts of sediment core V26-124. 394 records from (App 7) Relative contents of benthic foraminifera species in sediments accumulated during last 1000 years, Core ASV11-987. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 50 records from Leben in den Elbwiesen. 286 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C. 11 records from Nannofossil abundance of Hole 22-218. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 7208 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 7 records from Collection Malakologie - SMNG. 1289 records from Percentages of planktonic foraminifera species in sediment core V22-222. 27 records from Herbarium Senckenbergianum (FR) - Protista. 1304 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 495 records from (Table A.08) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (80-150 µm). 1035 records from Foraminifera abundance of Hole 24-237. 130 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 3536 records from Live (Rose Bengal stained) benthic foraminifera of surface sediments of the Persian Gulf (Table 1). 1 records from Orthoptera - SMF. 621 records from Biological Records Centre - UK Ladybird Survey data from iRecord. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 2728 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 781 records from RSPB - Bittern Annual Surveys in Britain 1990-2008 (SCARABBS). 700 records from (Table 3c) Foraminiferal distribution chart of ODP Hole 122-762C. 3524 records from Escarabajos y moscas de los bosques de niebla del sureste mexicano (Coleoptera: Scarabaeoidea; Diptera: Syrphidae y Calliphoridae). 18473 records from Australian Antarctic Division Herbarium. 6629 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 85 records from Schulgelände IGS Kaufungen. 83 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 1790 records from Planktic foraminifera abundance of Hole 9-77B. 1845 records from (Table 8C) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 8-5 through 15-3. 427 records from Planktic foraminifera abundance of Hole 76-533A. 19386 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 4540 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 2 records from Akita Prefectural Museum＋Hagfishes Specimens of Akita Prefectural Museum. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 22 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5116-2. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 62 records from Phytoplankton abundance during Akademik Vernadsky cruise AV22. 3538 records from (Table 4) Paleocene to Eocene planktonic foraminifera of DSDP Hole 29-277. 21172 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 33883 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 4380 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage (Australian Antarctic Data Centre). 12836 records from Planktic foraminifera assemblage in sediment core MD97-2142. 16 records from Occurrence of mammalia relicts at site Dorog. 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 376 records from Planktic foraminifera abundance of Hole 22-216. 691 records from Foraminifera abundance of Hole 24-236. 62371 records from MLZ Bird Collection (Arctos). 16344 records from Coleccion de sonidos ambientales. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 3201 records from Weevils of the Carpathians. 811 records from Amphibians and reptiles of Ireland. 1 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 166 records from BIRDRACE Die Düsselmöwen. 98 records from Planktic foraminifera abundance of Hole 74-528. 69 records from Planktic foraminifera abundance of Hole 52-418. 132 records from Range table from benthic foraminifers in ODP Hole 144-876A. 141 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 13325 records from Herbier du Bénin. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 3139 records from (Appendix A) Agglutinated foraminifers in ODP Hole 123-765C. 4 records from Akita Prefectural Museum＋Specimens of Class Maxillopoda of Akita Prefectural Museum. 38 records from Dinoflagellate abundance of Hole 71-512. 534 records from Leopard Seal census, Heard Island 1987/88. 10792 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 320 records from Scottish Wildlife Trust - Ants: Formica Exsecta Records from Abernethy RSPB. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 99 records from Streuobstwiese Stedar. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 60 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/543-5. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_15-CTD175. 10271 records from Carabidae of Poland. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 1364 records from Irish Collembola records. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 10234 records from Collection entomologique Barthélémy. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 19 records from Goethe-Hauptschule/Projekt I-10. 1 records from Wirtschaftsgrünland, Intensiv genutze Wiese. 14 records from Ostracoda abundance of Hole 44-392A. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/553-3. 5538 records from Colección Alberto Tinaut (Formicidae). 1470 records from EDIT - ATBI in Spreewald (Germany). 49406 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1985) (AfrOBIS). 191859 records from herbario. 894 records from CNAN/Arañas sinantrópicas. 6627 records from ATCC Fungi Collection Catalog. 22367 records from Bird Collection. 48 records from Relative abundance of planktic foraminifera in sediment core K11. 122 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 38 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB01 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 4 records from Occurrence of mammalia relicts at site Henauhof NW 2. 122 records from Occurrence of mammalia relicts at site Hunas. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 54 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629. 149 records from Total foraminifera counts of multinet PO247/2_MSN1372. 27 records from Total foraminifera counts of trap L3_92_45. 74 records from Faunal assemblage of sediment core TR149-36. 8 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 1045745 records from Herbarium of The New York Botanical Garden. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 12 records from Nannofossil abundance of Hole 31-299. 45 records from BIRDRACE Ohne Graureiher läuft nix!. 2000 records from Shellfish (ASJK_MS). 26 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thinocoridae. 268 records from Geometry of coccolith Coccolithus pelagicus in sediment core PS1113-1. 45 records from Collection Bryozoa - ZIM Hamburg. 60 records from (Table 5) Quality control of palynoclasts, palynomorphs and microplankton abundances in ODPHole 112-686B. 186 records from (3) Sea Surface Temperature (SST) reconstructed from the percentage of Neogloboquadrina pachyderma sinistral in sediment core MD02-2488 during the period 50-140 ka. 683018 records from The System-wide Information Network for Genetic Resources (SINGER). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 19 records from Antarctic Krill occurrence data from Japanese expeditions. 12 records from Microplankton abundance at bottle station SEPT-1999-K1. 301 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 2025 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 4971 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 4641 records from Lepidopterists Society Season Summaries 1973-1997. 13427 records from CNPE/Coleccion Nacional de Peces. 1101 records from Relative abundance of ostracods in sediment core Co1202. 60 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 14 records from Radiolaria assemblage in sediment core GIK23259-2. 2240 records from Derbyshire Biological Records Centre - Hemiptera Records 1969 - 2011. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 1 records from Dinoflagellate abundance of Hole 19-183. 893 records from (Table T1) Neogene dynoflagellate cyst occurrence in ODP Hole 186-1151A sediments. 2 records from Ireneopone gibber (Hym., Formicidae), a new genus and species of myrmicine ant from Mauritius.. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 30 records from A new species of Farlowella Eigenmann and Eigenmann (Siluriformes: Loricariidae), a stickcatfish from Bolivia.. 152 records from Planktic foraminifera abundance of Hole 16-159. 205 records from Planktic foraminifera abundance of Hole 29-284A. 672 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 1428 records from (Fig. 14) Distribution of dinoflagellate cysts in Early Cretaceous sediments of ODP Hole 103-638B in the North Atlantic. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 55690 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 8162 records from CRI - Herbário Pe. Dr. Raulino Reitz. 162150 records from Ditsong Museum. 35 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto11-19. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 96 records from Birdrace-federleser-Herford. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 62 records from Total foraminifera counts of multinet M21/4_MSN700. 144 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 2444 records from (Table 12A) Occurrences of planktonic foraminifers in selected samples of DSDP Holes 90-590 and 90-590A. 26079 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 337366 records from British Lichen Society - BLS Lichen Database: England. 12 records from (Table 3) Miocene biostratigraphy of the Hemmorian stage in Schleswig-Holstein. 104431 records from Field Museum of Natural History (Zoology) Fish Collection. 994 records from Biological Records In Essex - Bat records for Essex from 1971 - present.. 1594 records from Musée Vert ornithology collection. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 61 records from Total foraminifera counts of multinet M10/2_MSN229. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 85 records from Epifauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 4 records from "Am Riedert" im Westerzgebirge. 8540 records from Herbarium WRSL, Lichens Collection. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 83 records from Foraminifera species abundances from tow TT011_7-MOC66. 3161 records from Census in Agrimey forest reserve (southern Benin). 34 records from (Table 6B) Distribution of Mesozoic nannoliths at DSDP Hole 43-387. 156 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 23 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 10203 records from Coleoptera specimen database of Osaka Museum of Natural History. 1077 records from Percentages of planktonic foraminifera species in sediment core RC24-7. 1399 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-182. 11 records from Occurrence of mammalia relicts at site l´Abri Caminade-Ouest. 4 records from Occurrence of mammalia relicts at site Grotte Cotencher. 2 records from Planktic foraminifera abundance of Hole 54-421. 854 records from (Table T1) Abundance of stratigraphically important planktonic foraminifera in ODP Site 186-1150 sediments. 1444609 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 144 records from Ehmkendorf. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-20-5. 11 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 881 records from (Table 2) Planktic foraminifera and their diversity indices of sediment surface samples from the Atlantic Ocean. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-081. 14 records from Benthic macrofauna abundance of sediment core 12930-081. 23146 records from BC Coastal Waterbird Survey. 3578 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009 â sensitive records. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 2418 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 10 records from Oberservation of birds at station PS14/157 along 49° West. 46 records from Phytoplankton abundance at station DI183_11872#3. 37 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-6. 57 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 79 records from Ostracoda abundance of Hole 34-319. 202 records from Dinoflagellate cysts from sediment core PS1295-4. 129 records from Dinoflagellate cysts from sediment core PS2458-4. 1000 records from Diplopoda (JJHA-DI). 215 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 80 records from (Table 6) Distribution of the large, few-chambered Globigerinelloides species in the Lesches en Diois section. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 38 records from (Table 1) Chiasmolithus species and intermediate forms of ODP Holes 105-647A and 120-748B. 1513 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A. 61010 records from Fish Collection of Hokkaido University. 22 records from Sediment properties of core PLG95B_01BOXG. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 109 records from Dreilinden Gymnasium-Schulgelände. 123 records from Birdrace-SportfreundeTriller-Münster. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 2 records from Nannofossil abundance of Hole 6-50A. 13 records from Nannofossil abundance of Hole 11-103. 279 records from (Table 3) Relative abundance of benthic foraminifera in ODP Hole 112-681A. 361 records from Water mite collection of Pauli Bagge. 38 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832A. 40 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE272. 118 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 305 records from Flux data of NU2_trap (Table A1). 297 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 114203 records from UTA Herpetology. 12 records from New data on the European species of three genera Scelionidae (Hymenoptera).. 1973 records from Foraminifera abundance of Hole 61-462. 2066 records from Range table from benthic foraminifers in ODP Hole 159-959D. 139 records from Siliceous microfossil occurrence, Site 177-1093. 39 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 5 records from Occurrence of mammalia relicts at site Prekonoska Pecina. 229 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 57 records from Heidesee / Halle. 8 records from Planktic foraminifera abundance of Hole 94-611B. 279 records from Range table from planktonic foraminifers in ODP Hole 175-1077A. 175 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 78 records from Microfossil abundance of Hole 21-206. 59928 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 4649 records from Inventaire National du Patrimoine Naturel : Flore de Sologne. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 12065 records from Tromsø Museum, Bryophytes. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 520 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 69 records from Entdeckertour am Muldestausee 1/05. 6 records from Microzooplankton abundance and biomass at station TT043_7-20. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 8 records from Phytoplankton abundance at station Casma_2003-06-24_1, Casma, Peru. 78 records from Mammals (GNHM-MM). 2109 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 141 records from Plasm bearing foraminifera counts from multinet SO119_MSN1282. 163 records from Benthic foraminifera and nannofossil abundance of Hole 40-364. 2737 records from Gunma Museum of Natural History, Molluscan Specimen. 1 records from Nouvelles fourmis d'Afrique.. 3182 records from Finnish Entomological Database: Heteroptera. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 1035 records from National Museum Of Marine Science & Technology. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 277 records from Naturschutzgebiet Börstig bei Hallstadt. 77 records from Distribution of planktonic foraminifera of sediment core SH1972_1. 1811 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 821 records from Planktic foraminifera counts of sediment core V19-188. 240 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 20 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 2 records from Abundance of benthos infauna at station GIK23024-1. 20 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto20-28. 8008 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 36 records from Ecsenius caeruliventris and E. shirleyae, two new species of blenniid fishes from Indonesia, and new distribution records for other species of Ecsenius.. 164 records from Plasm bearing foraminifera counts from M35/1_MSN1064. 39 records from Sedimentological investigation on core V25-56. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 9 records from A new species of Pseudobagrus (Teleostei: Siluriformes: Bagridae) from southern China.. 4 records from Nannofossil abundance of Hole 8-75. 19 records from Meiofauna abundance in sediment core 12930-036. 4012 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 151-913B. 21 records from (Table 3) Paleotemperature estimates for ODP Hole 105-646B. 371 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001H. 3 records from Res Ligusticae XXII. Diagnosi di nuove specie di miriapodi cavernicoli. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 114 records from Flora. 49 records from Dörnberg. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1266. 82 records from Plasm bearing foraminifera counts from M35/1_MSN1050. 2 records from Nannofossil abundance of Hole 1-4. 6 records from Nannofossil abundance of Hole 10-91. 65 records from Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil.. 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 457 records from Microbial Observatory of the Laboratoire Arago. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 7 records from Distribution of planktic foraminifera of sediment core GIK23342-6 at stadium 5.5. 62 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/553-11. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC5. 159 records from Phytoplankton abundance at station CD47_0606C#7. 1677 records from Distribution of planktonic foraminifera in DSDP Hole 31-296 (Table III). 177 records from BIRDRACE Die Kielbris. 213 records from Coccoliths in sediment core PS1113-1. 103 records from Mammals (UWEP-MM). 3189 records from Propuesta para la realización de 37 fichas biológicas de las especies de herpetofauna incluidas en la NOM-059 presentes en la Península de Yucatán. 40 records from Range table from planktonic foraminifers in ODP Hole 172-1063A. 777 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 7032 records from EAN - Herbário Jaime Coelho de Moraes. 151010 records from Marie-Victorin Herbarium (MT). 464 records from Lepidoptera collection, NTNU, Trondheim. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 13884 records from (Figure 3) Range chart of dinocysts of ODP Hole 104-643A. 13 records from (Table 14) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-668A. 874 records from Flora acuática de Querétaro. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 31 records from Planktic foraminifera of sediment core GeoB1406-4. 4 records from Trap data WR2, 1648 m. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 112 records from Werl macht sich auf die Suche. 6 records from Ostracoda abundance of Hole 13-134. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 201 records from (Table 2) Relative abundances of calcareous nannofossils in ODP Hole 120-748A. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 20 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683B. 2820 records from (Figure 6) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-628A. 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 355 records from Tag der Artenvielfalt. 321 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 20755 records from pins. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 126 records from Total foraminifera counts of multinet PO231/3_MSN1336. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2177-3. 2 records from Smear slide analysis of sediment core GeoB7427-2. 127 records from BIRDRACE Southernmost Lakers. 34 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 720 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 126-793A. 2208 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 162 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano. 192425 records from Bryophytes of Ireland. 1833 records from DSMZ Fungi. 4 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Frank Haubrich. 14 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 508 records from Planktic foraminifera abundance of Hole 23-222. 3413 records from Planktic foraminifera abundance of Hole 23-219. 71 records from Foraminifera abundance of Hole 24-238. 40 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1072A. 17720 records from Collection Polychaeta SMF. 271 records from kisti_microb. 6 records from Pseudogramma xanthum, a new replacement name for a serranid fish from the subtropical South Pacific Ocean with description of the species.. 18970 records from Cowan Tetrapod Collection - Birds. 28038 records from HAS - Herbário Alarich Rudolf Holger Schultz. 637398 records from Données ONF Faune-Flore-FOnge. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 8470 records from (Table 12) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-714A. 14 records from R. Curry Collection. 9625 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 47 records from Occurrence of mammalia relicts at site Burgtonna. 441 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 582 records from Bioblitz 2013 Copenhagen Denmark. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 4 records from Sächsische Schweiz (Wehlener Gebiet). 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 84 records from BIRDRACE Vogelscheuchen. 2 records from Planktic foraminifera counts of multinet PS2616-5. 10 records from Concentration of siliceous microplankton in surface sediments, size fraction 20-40 µm. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 2 records from Nannofossil abundance of Hole 74-526. 34 records from (Table 6) Temporal variations of relative abundance of dead cells (in detritus, conglomerates and associated with Probocsia alata) of total number of living and dead cells of Emiliania huxleyi at Stations AH-2001-B3 and AH-2001-B3A. 80 records from Collection Copepoda - SMF. 86154 records from Naturalis Biodiversity Center (NL) - Coleoptera. 501 records from Planktic foraminifera assemblage in sediment core GIK17045-3. 1 records from Arthropoden aus südostalpinen Höhlen.. 4 records from Range table from planktonic foraminifers in ODP Hole 178-1099A. 4 records from A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar.. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 134 records from Birdrace-Team_Havelland-Havelland. 184 records from Abundance of calcareous dinoflagellates of sediment core GeoB3603-2. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 5 records from Nannofossil abundance of Hole 67-498A. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1 records from Karpfenteich, Klasse 6d. 269 records from BIRDRACE speedbirder. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 120 records from Total foraminifera counts of multinet PO247/2_MSN1387. 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 26 records from Nannofossil abundance of Hole 37-332A. 52359 records from Iziko. 1808 records from Ant'Phipoda Database (New records). 438 records from (Table 3) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-653A. 6188 records from (Figure 1) Range chart of planktonic foraminiferal species at ODP Hole 107-654A. 603 records from Polish Arctic Marine Programme (EurOBIS). 9 records from Microplankton abundance at bottle station SEPT-1999-K8. 71 records from Occurrence of mammalia relicts at site Teufelsbrücke. 16 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT008_5-CTD42. 1336 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 500 records from Plant (HBBG-PL). 21 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 14 records from Collection Pantopoda SMF. 1 records from Siphonaptera fossil - SMNG. 850 records from Riqueza específica y biogeografía de los corales hermatípicos de la sección sur del Golfo de California y las Islas Revillagigedo. 21 records from Nannofossil abundance of Hole 19-192. 418 records from Fossil (GNHM-FO). 243 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 18 records from Akita Prefectural Museum＋Cnidarians Specimens of Akita Prefectural Museum. 4 records from Description of lithologic section units of IODP Hole 325-M0034A. 245 records from Echuya Survey 2012. 1086 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC17-98. 535 records from Benthic foraminifera abundance of Hole 73-522. 65555 records from Mammals Specimens. 427 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 24286 records from Ross A. Layberry Observations. 399 records from CECT Spanish Type Culture Collection(Fungi). 13 records from Planktic foraminifera abundance of Hole 60-460A. 90 records from Planktic foraminifera abundance of Hole 24-233A. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 337 records from Zooplankton of the Eastern South Pacific, Universidad de Guayaquil, Ecuador (OBIS South America, SOUTH PACIFIC NODE). 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 45 records from Occurrence of mammalia relicts at site Erdhöhle. 709 records from Range table from benthic foraminifers in ODP Hole 139-857A. 13382 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2963 records from MfN - Diptera Collection. 76124 records from Lichen field notes, Oslo (O). 1 records from Nothrus biciliatus. 113 records from Total foraminifera counts of multinet M21/2_MSN627. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 22 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 2353 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 6328 records from Naturalis National Natural History Museum (NL) – Indo-Pacific Plio-Pleistocene fossils. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 287 records from BIRDRACE Pody und Co. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-49. 140 records from Dinoflagellate cysts counted on two fractions of surface sediment samples from stations A-9 to A-39. 16 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 52 records from Nannofossil abundance in sediment core PS1297-4. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 609 records from Herbier L. Mulon (BOUM). 230 records from (Table 1) Relative abundance of benthic foraminifera in ODP Hole 112-679D. 84 records from Seawater carbonate chemistry and processes during experiments with phytoplankton Emiliania huxleyi (strain Bergen 2005), 2010. 48 records from Pollen counts of sediment core GeoB9503-5. 39835 records from Lichen herbarium, Trondheim (TRH). 101 records from (Table S1d) Measured tomographic parameters for Oridorsalis umbonatus during ETM-2 for ODP Holes 208-1263C and 208-1262A. 107 records from RSPB - Crested tit wintering survey in the UK, 1992-1995 (RSPB). 2458 records from Colección de Ictiología. 2 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 1 records from Fourmis récoltées à Madagascar, par le Dr. Conrad Keller.. 6081 records from UNR Herpetology. 1391 records from Lichen herbarium, NMBU. 1 records from Arthropoden aus südostalpinen Höhlen.. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 1 records from Oribates angulatus. 1243 records from Crustacea ZMK. 98 records from Colección Nacional de Heliconias. 81 records from Birdrace-Die_Ornithomaten-Herford. 2300 records from Botanical Society of the British Isles - Demonstration set of data downloaded from the BSBI threatened plant database. 3 records from Sarcodine counts and carbon biomass at station TT011_4-CTD46. 68 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 25 records from Heavy minerals of sediment core PL94-08. 32356 records from Actualización de la base de datos del Atlas Mastozoológico de México. 750 records from (Table 20) Benthic foraminifera in early Miocene sediments of DSDP Hole 90-594. 42 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 336 records from (Table T1) Calcareous nannofossil abundance estimates of ODP Hole 210-1276A.. 1 records from Zetes longiusculus. 52 records from Isotope tracer experiment: meiofauna counts. 14605 records from DMNS Mammal Collection (Arctos). 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 230 records from Pilularia Globulifera distribution map in Denmark. 1 records from Miriapodi di alcune grotte della Campania. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 88018 records from NINA Vanndata øvrige arter. 470 records from Spiders_of_French_Guiana. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 8 records from Zoobenthos in surface sediments in the Yalta Bay. 4 records from Herpetology Collection. 4 records from Nannofossil abundance of Hole 31-293. 199 records from La fauna de Melolonthidae, Cerambycidae y Elateridae (Insecta: Coleoptera) de la reserva de la biósfera El Triunfo, Chiapas. 441 records from Planktic foraminifera distribution of sediment core 75KS76. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 2 records from Microzooplankton abundance and biomass at station TT050_11-4. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 2 records from Nannofossil abundance of Hole 66-489A. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 935041 records from NatureServe Network Species Occurrence Data. 25793 records from NCOS1959_Crustacea (OBIS China). 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 63 records from Range table from benthic foraminifers in ODP Hole 172-1062B. 181724 records from ArtenFinder. 322 records from Nannofossil abundance of Hole 15-147. 52 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 16 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/012-5. 67 records from (Table 2) Distribution of ostracodes in ODP Hole 107-650A. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 35 records from Akita Prefectural Museum＋Reptiles Specimens of Akita Prefectural Museum. 7881 records from Algaterra Types. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 60 records from (Table 2) Quantitative parameters of the Emiliania huxleyi population at the section along 70 m isobath carried out on 26 and 27 August 2001. 546 records from 20 Jahre Naturschutzgebiet Dreienberg. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 15902 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 2 records from Nannofossil abundance of Hole 1-4. 3 records from Analyses of the recent components of sediment core PS1010-1. 327284 records from Fungi (S). 191 records from Herpetofauna laguna El Tinije. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 51 records from Packer Collection / Xenochilicola bees, Chile. 36459 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 166 records from Plasm bearing foraminifera counts of multinet M21/1_MSN610. 3347 records from Mammal and Fish speciemens of Kumamoto City Museum. 1649 records from MfN - Trace fossils. 1612 records from Plant Specimens of Wakayama Prefectural Museum of Natural History. 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 3 records from Planktic foraminifera abundance of Hole 17-166. 37 records from Planktic foraminifera abundance of Hole 29-279. 1322 records from Planktic foraminifera abundance of Hole 29-284. 767 records from Phytoplankton abundance in surface water in February 1998, Paita, Peru. 465 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 131 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 182-1127B. 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 2419291 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 12509 records from The Bat Conservation Trust - Hibernation Survey. 44 records from "Schlechteberg" Ebersbach/Sa.. 420 records from (Table 4) Relative abundances of planktonic foraminifera in Pliocene sediments of ODP Site 161-975 in the Mediterranean Sea. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 19 records from (Table S2) Calcareous nannoplankton morphometric analyses performed of DSDP Hole 62-463 samples. 27290 records from Bird Monitoring Data. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 360 records from Küstenschutzwald. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 8 records from Aktion des Romain-Rolland-Gymnasiums. 32466 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2005) (AfrOBIS). 81 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 384 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 160 records from Schulgelände Schule auf der Aue, Münster. 14 records from Range table from planktonic foraminifers in ODP Hole 143-865B. 196 records from Range table from planktonic foraminifers in ODP Hole 162-986D. 15575 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 269 records from Range table from planktonic foraminifers in ODP Hole 182-1126C. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 1578995 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 157 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera of surface sediment off Morocco (Table 6). 16 records from A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species.. 113482 records from KUBI Ornithology Collection. 13909 records from Albany Museum. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 1 records from Streuobstwiese Alt Necheln. 7 records from Solifugae Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 129 records from Total foraminifera counts of multinet M12/3_MSN561. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 14 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 4 records from Nannofossil abundance of Hole 29-284A. 7 records from Nannofossil abundance of Hole 49-409. 8 records from Diatom abundance measured on water bottle samples at station PS58/091-4. 15 records from Meiofauna abundance in sediment core 54301-016. 342 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 25727 records from Irish National Badger Sett Database. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 122 records from Total foraminifera counts of multinet M21/2_MSN651. 98 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1381. 1371 records from (Appendix 2-7) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 59-451 in the western Pacific Ocean. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 75 records from Foraminifera species abundances from tow TT007_8-MOC15. 1 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 3666 records from (Table 5) Stratigraphic ranges of selected Oligocene to earliest Miocene planktonic foraminifers in ODP Hole 115-709A. 42 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Florian Werner. 48 records from Planktic foraminifera abundance of Hole 6-47. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 1803 records from Vertebrate specimens of Jyväskylä University Museum. 116772 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 82 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_6-CTD67. 17 records from Taxonomy and distribution of the ant Cataglyphis setipes (Hymenoptera: Formicidae). 138 records from (Table 2a) Species composition of planktonic foraminiferas in bottom sediments from Core AK6-434-1. 1035 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 1184 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 73821 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1986) (AfrOBIS). 5552 records from MAR - Herbário do Maranhão. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 98 records from Occurrence of mammalia relicts at site Felsställe. 542 records from Planktic foraminifera abundance of Hole 18-175. 135656 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009. 365 records from Greater Manchester Ecology Unit - Distribution of Bats in Greater Manchester. 632 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 7 records from Additions to the myxobiota of the Åland Islands. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 134 records from Total foraminifera counts from M35/1_MSN1046. 13 records from Planktic foraminifera counts of multinet PS31/002. 679 records from Inventaire National du Patrimoine Naturel : Programme national espèces végétales de la Directive Habitat. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 741 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 358 records from (Appendix 3, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core BMR96GC21 in the southeast Indian Ocean. 3550 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 5 records from (Table T9) Calcareous nannofossil stratigraphy of ODP Hole 198-1211C. 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 184 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 51499 records from NRM-Fishes. 16282 records from Atlas der Raubfliegen Deutschlands - database. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 26835 records from Herbario Pontificia Universidad Javeriana. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 40 records from Nannofossil abundance of Hole 21-205. 78 records from Nannofossil abundance of Hole 27-262. 1376 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 1584 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 1614 records from New Brunswick Museum Collection. 3 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Frederike Proewe. 66 records from Planktic foraminifera assemblage in sediment core GeoB1113-4. 380 records from Artenvielfalt der Nordsee - Helgoland. 3637 records from Lepidoptera collection of NW Europe. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 111 records from Birdrace-Uhulogen-Lippe. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 113 records from Plasm bearing foraminifera counts from M35/1_MSN1062. 7 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 39650 records from (Table T1) Miocene planktonic foraminiferal stratigraphy of ODP Hole 184-1148A. 142 records from (Appendix C) Average nannofossil abundances in mid-Pliocene sediments from the equatorial Atlantic. 153299 records from Insekten Sachsen. 1 records from Damaeus torvus. 407 records from Myriapoda - SMF. 2794 records from Diversidad bentónica de la laguna Celestún, Yucatán. 3 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 1154 records from Collection Plecoptera - SMF. 205599 records from CABI Bioscience Fungus Collection. 69009 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 143811 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations (OBIS Canada). 100429 records from ICN - Herbário do Instituto de Ciências Naturais. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 46 records from Liether Park (LMS), 5a. 55 records from Seeufer ehem. BUGA-Gelände. 91 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-765C. 9322 records from (Figure 3) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548A. 2320 records from Planktic foraminifera assemblage of sediment core ELT49.018-PC. 1073 records from Relative abundance of planktic foraminifera in sediment core RC17-69. 6 records from Planktic foraminifera abundance of Hole 23-226. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 9 records from Abundance of radiolaria at station UT99-24-1. 4500 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 5815 records from Coleoptera of Białowieża Forest. 870 records from Percentages of planktonic foraminifera species in sediment core V22-38. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/088-4. 10 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2159-3. 145 records from Ostracoda abundance in DSDP Leg 87 holes. 11 records from Benthic macrofauna abundance of sediment core 13200-017. 134 records from Planktic foraminifera counts of sediment core V19-202. 4778 records from SO-Polylist. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 2524 records from (Table 13) Ranges of benthic foraminifers through the early to middle Miocene in ODP Hole 115-715A. 13842 records from BCCM/LMG - Laboratory of Microbiology Gent Bacteria Collection. 568 records from Planktic foraminifera assemblage in sediment core SU92-21. 459 records from NSG Karwendel. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 6 records from (Table 1d) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the Late Neopleistocene - Holocene activity phase of the Keli Volcanic Highland. 2312 records from Mycological collection of the National Museum. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 1395 records from Birds - Wild Birds (KIDR-BI). 677 records from Insect colletion. 154 records from Dermaptera in the icipe collection. 178 records from RSPB - Corn bunting surveys on the Western Isles. 1851 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 1 records from Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time!. 1905 records from BioGIS - Reptiles - INPA database. 1641 records from NCSM PaleoBotany Collection. 36 records from Selz (Ingelheim am Rhein). 6 records from Fließgewässeruntersuchung am Haselbach. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 79 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1375. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD85. 30 records from Microzooplankton abundance measured on water bottle samples at station PS65/553-3. 2628 records from GEO Hauptveranstaltung Tirol (Innsbruck). 929 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 28 records from (Appendix A3) Paragloborotalia morphometric and coiling data from Oligocene sediments of ODP Site 199-1218 in the equatorial Pacific. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 2310 records from (Table 15A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-593. 77605 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 7380 records from University of Ghent - Zoology Museum - Invertebratacollectie. 34 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 2 records from Schistura papulifera, a new species of cave loach from Meghalaya, India (Teleostei: Balitoridae).. 7 records from Analyses of the recent components of sediment core PS1402-2. 1092 records from Range table from planktonic foraminifers in ODP Hole 155-936A. 37 records from Range table from benthic foraminifers in ODP Hole 146-891A. 745 records from Gunma Museum of Natural History, Mammal Specimen. 850 records from RSPB - Crossbills, Distribution survey in Great Britain, 1995-2005 (RSPB). 9256 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 968 records from (Table T17) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P14-P18. 14 records from Microzooplankton abundance and biomass at station NBP97-03-11-1. 8 records from Nannofossil abundance of Hole 49-412A. 296 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE233. 6 records from Relationships of the New World cichlid genus Hypsophrys Agassiz 1859 (Teleostei: Cichlidae), with diagnoses for the genus and its species.. 333 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Charadriidae. 13898 records from TEPB - Herbário Graziela Barroso. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 765 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 433 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 33070 records from CSIRO Ichthyology provider for OZCAM. 79186 records from All Ireland Non-Marine Molluscan Database. 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 124 records from Total foraminifera counts of multinet M21/1_MSN620. 153 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1909-2. 1 records from Microplankton counts and carbon biomass at station TT008_6-CTD64. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-18-5. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 2 records from Wie viel Natur gibt es im Park?. 16 records from Nannofossil abundance of Hole 24-235. 48 records from Nannofossil abundance in sediment core PS1314-4. 73 records from Macrofauna abundance in surface sediment sampled during cruise DI222/2. 1309 records from Mongolian Plant (MMNH-PL). 18 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 16 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 140 records from Distribution of planktonic foraminifera of sediment core SH1972_17. 32 records from (Table 4) Carbonate and washed residue weight percentages in ODP Hole 121-758B. 56081 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 154124 records from Arizona State University Lichen Collection. 408 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 275 records from Wald und Wiese am Buchwald. 29362 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 15 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 2 records from Nannofossil abundance of Hole 3-17A. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 31 records from Pollen profile V and Ausfluss at Krumbach, Germany. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 1099940 records from DOF 2001-2006. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 13616 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 138 records from Total foraminifera counts of multinet M11/1_MSN520. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-23-2. 219 records from (Table 2) Stratigraphic distribution of planktonic foraminifera from the middle Miocene to upper Miocene in ODP Hole 134-832B. 390 records from (Table 3) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Cismon core. 2760 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 96489 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 12 records from Microplankton abundance at bottle station SEPT-1999-K4. 122 records from A contribution to the study of the Lower Volga center of scarab beetle diversity in Russia: checklist of the tribe Aphodiini (Coleoptera, Scarabaeidae) of Dosang environs. 33 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 459 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_5-CTD56. 5 records from Pollen record of a sediment profile from Lake Teletskoye. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1403-1. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 20 records from (Table 2) Abundance and biomass of the main microplankton biota components in the Murmansk coastal pelagic zone in March 1998. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 22 records from Abundance of Globorotalia menardii of sediment core GeoB2822-2. 958 records from (Table 6) Planktonic foraminifera in ODP Holes 139-856A and 139-857A. 4 records from MfN - Fossil vertebrates II. 101 records from Nannofossil abundance of Hole 64-476. 3772 records from Fish (KIWE-PI). 2178 records from Flora exsiccata Bavarica. 36 records from Abundance of algae in the Aral Sea. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 207 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 3477 records from Aves laguna El Tinije. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 1042 records from Planktic foraminifera abundance of Hole 37-333. 45 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 11 records from Occurrence of mammalia relicts at site Rotselaar. 1256 records from Foraminifera abundance of Hole 64-481. 7 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 24 records from Range table from planktonic foraminifers in ODP Hole 170-1039A. 1 records from Damaeus auritus. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cariamidae. 23099 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 90 records from Range table from benthic foraminifers in ODP Hole 146-889B. 424 records from Taxonomic Revision of the Ant-Acacias (Fabaceae, Mimosoideae, Acacia, Series Gummiferae) of the New World. 764 records from BioGIS - Fish - INPA database. 663 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Lacewings and Allies (BNHS) - 1942-2009. 4318 records from Diptera Collection of Museum and Institute of Zoology PAS. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 101 records from BIRDRACE nabu-rhein-main.de. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 12 records from Abundance of radiolaria at station LV28-44-1. 5 records from Nannofossil abundance of Hole 3-22. 2 records from Nannofossil abundance of Hole 14-144A. 19 records from (Table 2) Range chart of calcareous nannofossils from Maud Rise sediment cores. 214 records from Planktic foraminifera counts of sediment core V27-86. 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 4132 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 302 records from Kohlstattbrunnental. 122 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 494248 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 3 records from Nouvelles fourmis de Madagascar.. 123845 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 238 records from Abundance of planktic foraminifera at CTD station PS55/081-1. 28 records from Smear slide analysis on sediment core GeoB4217-5. 1638 records from (Table 1) Relative abundances of benthonic foraminifera in ODP Site 116-717. 1185 records from (Appendix A) Foraminifera and stable carbon and oxygen isotope record of ODP Site 105-646. 6 records from Occurrence of mammalia relicts at site Barova Cave. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 19 records from Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific.. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 53 records from BIRDRACE Taubenhaucher. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 152 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/043-2. 279 records from Koleopterologen am Bausenberg. 177 records from Donauinsel des BN bei Entau. 2 records from Nannofossil abundance of Hole 74-525A. 13 records from Benthic macrofauna abundance of sediment core 13200-008. 146624 records from Plants of Papua New Guinea. 389 records from (Table 2) Distribution of planktonic foraminifera in DSDP Hole core 90-594. 151 records from Planktic foraminifera abundance of Hole 11-104. 1851 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 44 records from Flora und Fauna in unserer Kita. 1445 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments. 950 records from (Table 9) Distribution of planktonic foraminifera in the early Pliocene to Holocene section of ODP Hole 149-900A. 1116 records from CUBA:Herbario del Jardín de los Helechos, Centro Oriental de Ecosistemas y Biodiversidad, Santiago de Cuba: BSC-Pteridophyta. 80846 records from Colección de Lepidópteros del Museo de Zoología 'Alfonso L. Herrera', México (MZFC, UNAM). 54 records from Planktic foraminifera abundance of Hole 15-146. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 185 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 180 records from Phytoplankton abundance off Guañape islands in Juli 2003, Peru. 819 records from (Table T4) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P7-P8. 1735 records from The Flora of County Clare. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 68304 records from IICT Herbário LISC. 150 records from Vegetatively propagated Allium collection. 51 records from Planktic foraminifera assemblage in sediment core GIK23066-2. 14882 records from NCSM Mammals Collection. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 103 records from Wasserwerkspark (Chemnitz). 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 933 records from (Table T3) Planktonic foraminifera abundance of ODP Site 170-1041 sediments. 27 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-50. 279 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 197 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station SEPTEMBER-1995-D4. 3304 records from Planktic foraminifera abundance of Hole 41-369A. 11 records from Oberservation of birds at station PS14/145 along 49° West. 13230 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 43 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1017. 7360 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 2222 records from UWYMV Bird Collection (Arctos). 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 4567 records from Herbarium WRSL, Main Collection. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 7774 records from BioGIS - Hamaarag. 13 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 536 records from Walldorf-Wiesloch: "Natur über den Gleisen". 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 23 records from Planktic foraminifera abundance of Hole 29-284A. 1 records from Planktic foraminifera abundance of Hole 54-424A. 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 4 records from Pachycondyla nigrita and related species in Southeast Asia.. 260776 records from DINA. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 5 records from Occurrence of mammalia relicts at site Victoria Cave. 1425 records from (Fig. 12) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 50-416A in the North Atlantic. 106920 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 9 records from Microzooplankton abundance and biomass at station TT043_6-1. 26 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 56 records from Nanoplankton abundance at station GeoB2021-3. 2 records from Nannofossil abundance of Hole 58-442B. 10898 records from Himenópteros Parasíticos en México (UANL). 613 records from Distribution of dinoflagellate cycst at ODP Site 123-765 (Table 1). 503 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Invertebrados. 226 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 763 records from Bisons Collection. 184156 records from The Flora of County Waterford. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 16324 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 1 records from Celaeno rhodomela. 1 records from Arthropoden aus südostalpinen Höhlen.. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 500808 records from Neptune Deep-Sea Microfossil Occurrence Database. 2913345 records from Especímenes INBio. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 258 records from BIRDRACE Raumpatrouille Oriolus. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 24 records from Counts (2) of calcareous dinocysts along profile Stevns-Klint. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 88 records from Microfossil abundance of Hole 16-157. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/091-4. 290 records from Planktic foraminifera counts of sediment core RC11-134. 2084 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for sediment core R657. 65 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827A. 1373 records from Finnish Entomological Database: Araneae. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 61 records from Wälder im Hainbachtal. 69 records from Faunal assemblage of sediment core GS7603-7. 5 records from Nannofossil abundance of Hole 6-53A. 642 records from Planktic foraminifera counts of sediment core V22-196. 83 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Cumacea.. 2118 records from Flora de macroalgas del litoral oaxaqueño. 156948 records from NBI. 2 records from Benthic foraminifera abundance of Hole 42-376. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 1257 records from Faun. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 56302 records from Kathryn Kalmbach Herbarium. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 1695 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 76 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 7 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC6. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 69 records from Naturpark Kottenforst-Ville 17.6.09. 349178 records from AMNH Herpetology Collections. 304 records from Planktic foraminifera counts of sediment core V29-173. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 17369 records from MfN - Auchenorrhyncha Collection. 346511 records from ARGOS Satellite Tracking of animals. 1794 records from Elephant Seal Sightings, Heard Island. 176 records from INSECT COLLECTION. 6782 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 85 records from Range table from benthic foraminifers in ODP Hole 154-929B. 2651 records from KTU Pteridophyta. 2193 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 3275 records from Quantitative Phytoplankton data from Irish lakes (EPA). 371 records from Planktic foraminifera abundance of Hole 63-470. 38 records from Microfossil abundance of Hole 21-206C. 3318 records from ZOOLOGIA_FCNO_UDEC_CL Foraminiferos_01 (OBIS South America, SOUTH PACIFIC NODE). 29876 records from European Moth Nights. 316 records from Moss species from Heard Island, 1987 and 2000. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 90 records from Quaternary radiolarians from offshore eastern New Zealand, ODP Leg 181, Site 1123, relative abundances. 86774 records from Queen Victoria Museum Art Gallery provider for OZCAM. 49 records from New species of the amphiliid catfish genera Amphilius, Doumea and Phractura and the taxonomy of Paramphilius from West Central Africa (Siluriformes, Amphiliidae).. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 1 records from Nothrus palliatus. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 15 records from Urwald 2 (Bad Waldsee). 174 records from Total foraminifera counts from multinet M31/3_MSN915. 227 records from Total foraminifera counts from multinet M31/3_MSN916. 52 records from Total foraminifera counts of multinet M21/4_MSN713. 133 records from Total foraminifera counts of multinet PO247/2_MSN1379. 134 records from (Table 1) Benthic foraminiferal distribution at ODP Site 127-794. 668 records from Phytoplankton abundance during OCEANIA cruise Oceania90. 1296 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 79 records from Occurrence of mammalia relicts at site Rislisberghöhle. 83 records from Planktic foraminifera abundance of Hole 40-361. 324 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 40 records from The identity of Pseudecheneis sulcata (M'Clelland, 1842), with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China.. 7 records from (List 1) Fossil record of Mollusca in Schleswig-Holstein, Germany. 2 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 1174 records from PReCAST Marine Mammal Sightings. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 40 records from Öhmdwiesen und Göldern (Konstanz). 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 54 records from Biotope im Schulumfeld. 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 34 records from Foraminifera species abundances from tow TT007_9-MOC18. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 1 records from Hypochthonius pallidulus. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 1 records from Nothrus convexus. 22854 records from National Botanic Garden Belgium - Myxomycetes. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 630 records from (Figure 3) Distribution chart of benthic foraminifers in ODP Site 126-790. 1536 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A. 311 records from Avena wild species VIR Herbarium. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 112 records from Total foraminifera counts of multinet M33/1_MSN1029. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 1726 records from KTU Pinophyta. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 40 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 38998 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 4 records from Nannofossil abundance of Hole 9-81. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/565-1. 1431 records from (Table 10) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-712A. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 525 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 272 records from Dinoflagellate abundance of Hole 81-555. 4 records from Microzooplankton abundance and biomass at station TT054_17-21. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 18 records from Smear slide analysis on sediment core GeoB4206-1. 12 records from Nannofossil abundance of Hole 74-528A. 137 records from Planktic foraminifera counts of sediment core V28-25. 5 records from The nematoda fauna of sediment samples of Sarso Islands, Red Sea (Table 5). 214 records from Benthos abundance in surface sediment sampled during cruise ANT-V/1. 101 records from Relative abundance of coccosphere-units of sediment core GIK23411-5. 5817 records from SMNS Palaeontological collection - Amber. 6 records from Nannofossil abundance of Hole 7-63. 4 records from Nannofossil abundance of Hole 77-540. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 823 records from Planktic foraminifera counts of sediment core V17-165. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 2464 records from (Table 2) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-698A. 178 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 9558 records from Modern planktic foraminifera assemblage from surface sediment samples used as reference data set for the reconstruction of Atlantic sea surface temperatures during the last glacial maximum (LGM). 329 records from Fig. 11: Benthic foraminifera assemblage of sediment core MD97-2131. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D2. 463 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 248 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 3219 records from (Figure 6) Planktonic foraminifera distribution in ODP Hole 130-803D. 10175 records from Seil Natural History Group - SNHG Biological Records Dataset. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 1427 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 15 records from Description of lithologic section units of IODP Hole 325-M0032A. 11903 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 6 records from Sediment properties of core PLG93_BCORE1. 582 records from (Table 2) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 3-21 from the Rio Grande Rise, South Atlantic Ocean. 166 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 240 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru. 213 records from Poliquetos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMUV). 3096 records from Biological Records Centre - Mosquito Recording Scheme. 33 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ramphastidae. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 335 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1170D sediments. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 102 records from (Figure 3) Selected benthic foraminifera measurements from sediment core AvH248260-1, Ameralik Fjord, SW Greenland. 5 records from Two new species of Exallonyx Kieffer (Hymenoptera: Proctotrupidae) from China, with a key to Chinese species.. 226 records from Molecular and morphological characterisation of new species in the trapdoor spider genus Aname (Araneae: Mygalomorphae: Nemesiidae) from the Pilbara bioregion of Western Australia. 94 records from (Appendix 4) Calcareous nannofossils in ODP Hole 113-689B. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 38 records from Phytoplankton abundance at bottle station A1/52. 497 records from Relative abundance of Quaternary foraminifera of sediment core CRP-1 (App. 1). 268160 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 138 records from Relative abundance of live benthic foraminifera of sediment core M5/2_107MC. 1069 records from ZFMK Sound Archive. 3 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 2265 records from Algae, Specimens, Agder naturmuseum (KMN). 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 5 records from (Table 1) Late Maastrichtian calcareous nannofossils in DSDP Hole 22-212. 17 records from MVZ Herp Observations (Arctos). 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 261 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 434 records from (Table 4) Benthic foraminiferal community at DSDP Hole 94-609B. 88537 records from PACA-AGP - Herbarium Anchieta. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 7551636 records from BirdLife Australia, Birdata. 1087 records from SMNS Palaeontological collection - Tertiary and quaternary invertebrates. 127 records from Birdrace_Schräge_Vögel-Herford. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 198 records from Total foraminifera counts from M35/1_MSN1047. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1 records from Celaeno obsoleta. 52381 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 2 records from Neue Milbenarten aus Kärnten. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 169 records from Expedition "Schulgelände". 114 records from BIRDRACE VIE will rock you!. 420 records from Phytoplankton abundance in surface water in November 1997, Ilo, Peru. 1 records from Nothrus bicarinatus. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 378 records from Size of planktic foraminifera at CTD station PS55/077-1. 244 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN889. 159 records from Total foraminifera counts of multinet M21/6_MSN789. 233 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 56 records from Microzooplankton abundance measured on water bottle samples at station PS65/470-1. 8 records from Nannofossil abundance of Hole 60-458. 288 records from Gorgonacea specimens of Kuroshio Biological Research Foundation. 17 records from (Table 2h) Nannofossil distribution chart of petroleum well Swan-3St. 3422 records from Distribución y aspectos taxonómicos de los corales pétreos (Anthozoa: Scleractinia) del Pacífico mexicano. 16 records from Description of lithologic section units of IODP Hole 325-M0057A. 12 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5110-4. 572 records from Planktic foraminifera counts of sediment core V04-32. 1167 records from Macroinvertebrate Data BOKU. 35 records from Range table from planktonic foraminifers in ODP Hole 139-858D. 345 records from Range table from nannofossils in ODP Hole 199-1218A. 30409 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 41 records from Nine genera of Eucnemidae (Coleoptera) new to Peru, with a key to Peruvian genera. 58031 records from Colección nacional de zoología. 17520 records from Arthropod collection, Tromsø Museum. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 180 records from Paul-Gerhardt-Schule Dassel. 126 records from BIRDRACE Die Schwenker-Birder. 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 97 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1383. 4 records from Microzooplankton abundance and biomass at station TT054_26-21. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-28-3. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 936 records from Bats of Poland. 1789 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 6 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 31 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 288 records from Planktic foraminifera abundance of Hole 94-610A. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 37 records from A brief review of Triplophysa (Cypriniformes: Balitoridae) species from the Tarim Basin in Xinjiang, China, with description of a new species.. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 671 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD59. 482 records from Kühmark bei Wetzlar. 39 records from Ostracoda abundance of Hole 24-238. 121 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 510 records from Planktic foraminifera counts of sediment core V20-242. 250 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 3702 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 20114 records from Molluscus specimens of Toyohashi Museum of Natural History. 9 records from (Table 4) Abundance of microalgae in sinking sedimentary material from sediment traps in the northeast Black Sea in September-October 1999. 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1994-D4. 48 records from Planktic foraminifera abundance of Hole 25-241. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 56 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 2324 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 76 records from Live (Rose Bengal stained) benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 90 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from planktic foraminifera. 1 records from Occurrence of mammalia relicts at site Ejstrup. 5 records from Range table from benthic foraminifers in ODP Hole 181-1120C. 406 records from (Table 4) Distribution of foraminifera in the Miocene section of ODP Hole 133-816C. 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 751 records from (Table T5) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1212B, Shatsky Rise, Pacific Ocean. 872 records from Colección de Entomología - Hymenoptera - Parasitica. 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 24972 records from Colección de Herbario. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 8220347 records from OEH Atlas of NSW Wildlife. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 231131 records from MVZ Mammal Collection (Arctos). 1 records from On the Chilopoda from Turkey. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 66 records from Langes Tannen(LMS), Klasse 5d. 75 records from BIRDRACE Die Kartoffelsäcke. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 150 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 10061 records from Collembola collection of Arne Fjellberg, Norway. 1 records from Hoplophora carinata. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 101 records from Birdrace-Herford-Birder-Herford. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 133 records from Abundance of planktic foraminifera at CTD station PS55/018. 15663 records from Collection Herpetologie - SNSD. 39 records from Planktic foraminifera abundance of Hole 28-265. 73 records from Fossil (JNHM-FO). 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 41884 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 161 records from Total foraminifera counts of multinet M21/3_MSN671. 4 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 318 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 13746 records from CNIN/Coleoptera. 4 records from Oribatids from Switzerland IX (Acari: Oribatidae, Mycobatidae 2) (Acarologica Genavensia CI). 92 records from Nottekanal, Klasse 7 - 10. 255 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 319 records from Dinoflagellate abundance of Hole 38-338. 17966 records from Ornithology Collection. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru. 4 records from Nannofossil abundance of Hole 5-32. 39 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI231. 7414 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 15918 records from BANDASCA, BAse de DAtos sobre SCArabaeidae. 12 records from Chenopodieae. 17876 records from Mycology Herbarium, Trondheim (TRH). 978 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 201 records from Mycological collections of the University of Tartu. 3 records from Nannofossil abundance of Hole 20-199. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 12 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-1. 23315 records from Gwaii Haanas Invertebrates (OBIS Canada). 1309 records from Benthic foraminifera distribution of sediment core BP01-62/06. 83 records from Frau Voss. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 5583 records from All observations extracted from the Flora of Northumberland and Durham 1831. 3509 records from Entocytheridae (Ostracoda) World Database. 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 123006 records from Finnish Entomological Database: Diptera. 44 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 308 records from Phytoplankton abundance during G. M. Dannevig cruise GMD91/10. 55 records from "Schule am Inselsee" Güstrow. 6 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 128 records from (Table 5) Distribution of the large, many-chambered Globigerinelloides species in the Calabianca section. 2 records from Range table from planktonic foraminifers in ODP Hole 139-855D. 131 records from Siliceous microfossil occurrence, Site 177-1092. 14830 records from Parasitic Platyhelminthes Collections. 102 records from Streuobstwiese RSG (Cham). 2500 records from Zooplankton (NSMK-ZP). 182 records from Range table from benthic foraminifers in ODP Hole 182-1128B. 29367 records from Geographic distribution of dinoflagellate cysts in surface sediments. 67 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 85 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Recurvirostridae. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 777 records from INRA-Versailles Arabidopsis natural variants. 1355 records from Planktic foraminifera abundance of Hole 18-173. 66 records from Range table from planktonic foraminifers in ODP Hole 151-909A. 433 records from (Table S1) Palynology of IODP Hole 302-M0004A. 871 records from Benthic foraminiferal assemblages (dead), surface data. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 324 records from Total foraminifera counts from multinet M32/5_MSN974. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 105 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1372. 27 records from A new species of the gobiid fish Trimma from the Western Pacific and Northern Indian Ocean coral reefs, with a description of its osteology.. 44998 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 7000 records from CCBER Ornithology Collection. 1 records from On the Chilopoda from Turkey. 1 records from Murcia ephippiata. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 9 records from Countryside Council for Wales - Sightings & Miscellaneous Data from Countryside Council for Wales (CCW), 2008 onwards. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 274 records from Bernhardsthal. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 199 records from Palynomorpha in sediment core PM9462-4 from the Laptev Sea. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 48 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 109 records from Broadland Environmental Services Limited - Reptile distribution along the River Bure, Broadland (2010). 141 records from (Table 2) Relative abundance of benthic foraminifera in ODP Hole 112-680B. 11700 records from (Figure 4) Distribution of benthic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 45 records from Pfrimmersbachtal. 39 records from Range table from planktonic foraminifers in ODP Hole 139-856B. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 51 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 37 records from Plasm bearing foraminifera counts of multinet M27/2_MSN879. 20 records from Occurrence of mammalia relicts at site Niederlehme. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 8 records from Mean values of fractionated primary production and protozoan abundance from the photic layer collected at 50 m depth in Mejillones Bay. 6 records from A new genus and five new species of Astieae (Araneae: Salticidae) from Australia, with remarks on distribution. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 12 records from Benthic macrofauna abundance of sediment core 13200-020. 15 records from Abundance of Elminius modestus in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 46 records from Nannofossil abundance of Hole 26-254. 9 records from Nannofossil abundance of Hole 26-255. 15 records from Benthic macrofauna abundance of sediment core 13077-093. 421 records from Planktic foraminifera counts of sediment core RC09-162. 599 records from Planktic foraminifera counts of sediment core V26-41. 81 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part I. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 26 records from Calcareous dinocysts in ODP Hole 80-550B, part 1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-33-5. 5 records from Abundance of radiolaria at station LV28-66-1. 3 records from Nannofossil abundance of Hole 9-80. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 18 records from Phytoplankton abundance at station Rigel_6_2005-04 in April 2005, Chipana, Chile. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 18 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE218. 2698297 records from Eremaea. 626 records from (Table 2) Benthic foraminifera distribution in sediment core ASV11-880-3. 6 records from Planktic foraminifera abundance of Hole 4-24. 1 records from Dinoflagellates, pollen and spore abundance of Hole 29-281. 3329 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 11 records from Microzooplankton abundance and biomass at station TT045_2-1. 51 records from Coccoliths in sediment core PS1295-4. 544 records from (Table 1) Stratigraphic distribution of new marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B. 686 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 364 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 17979 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 171 records from Foraminifera abundance of sediment core C1960.201. 3 records from Analyses of the recent components of sediment core PS1401-2. 152 records from Sonnentaugemeinschaft. 180 records from Entdeckertour am Muldestausee. 30 records from Range table from planktonic foraminifers in ODP Hole 152-916A. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 900 records from Percentages of planktonic foraminifera species in sediment core V30-36. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station APRIL-1995-D4. 30 records from Occurrence of mammalia relicts at site Stematia. 78 records from Range table from planktonic foraminifers in ODP Hole 167-1019C. 94 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 1420 records from Planktic foraminifera abundance of Hole 49-407. 35 records from Range table from benthic foraminifers in ODP Hole 181-1124C. 255439 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Carabodes coriaceus. 822 records from Isotope tracer experiment: nematode abundance. 3772 records from BOS Arthropod Collection of University of Oviedo (Spain): Opiliones. 3341 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 77 records from Plasm bearing foraminifera counts from multinet SO119_MSN1303. 25 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru. 14 records from Two new glyptosternine catfishes (Teleostei: Sisoridae) from Vietnam and China.. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 76 records from Birdrace-Birding_for_Nature-Bonn. 1553 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 18 records from Phytoplankton abundance at bottle station GOM3/1. 42 records from Stadtwald Heide. 46 records from Aktion Wiese und Wegrain Gitzenheide. 2224 records from Cambridgeshire & Peterborough Biological Records Centre - Cambridge Lichen group data held by CPBRC.. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 458 records from Barley French National Collection. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 117 records from Naturschutzgebiet Kochertgraben. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 49133 records from MBML-Herbario - Herbário Mello Leitão. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 1 records from Oribates picipes. 86 records from Naturerlebnisraum Koppelsberg (Plön). 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 6 records from Microzooplankton abundance and biomass at station NBP97-03-09-1. 128 records from Phytoplankton abundance at station CD47_2805C#5. 34 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 50 records from Artensuche auf den Elbwiesen in Radebeul. 95 records from BIRDRACE BiBi. 783 records from Phytoplankton abundance in surface water during cruise CD61. 50 records from NABU-Fläche am Bösselhausener Weg. 950 records from (Appendix 2) Late Cretaceous benthic foraminifera of ODP Site 207-1259. 1620 records from (Figure 5) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-513. 85 records from Range table from planktonic foraminifers in ODP Hole 151-909C. 689 records from Range table from planktonic foraminifers in ODP Hole 152-919B. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 1 records from The ant genus Pseudaphomomyrmex Wheeler, 1920 a junior synonym of Tapinoma Foerster, 1850.. 1423 records from Raw counts of dinoflagellate cysts of sediment core DP30PC. 1433 records from (Appendix Table 1) Relative abundances of calcareous nannofossil in the total assemblage of ODP Hole 177-1090D. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 225 records from Nannofossil abundance of Hole 15-154A. 3 records from Nannofossil abundance of Hole 22-212. 47 records from Nannofossil abundance of Hole 86-577. 5 records from Nannofossil abundance of Hole 67-499B. 5 records from Diatom abundance measured on water bottle samples at station PS58/043-2. 42 records from (Appendix 7) Abundance of Neogloboquadrina pachyderma in sediment core MD01-2444. 234 records from (Table 2) Selected planktonic foraminiferal species and other microfossil data for sedimentcore P69. 326 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 88 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2214-1. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 69 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 47 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 414 records from (Table A a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-22 at 2000 m water depth. 666 records from (Table 2) Species composition of agglutinated foraminifers from the abyssal zone of the Pacific Ocean. 97 records from CNIN/Tipos Hymenoptera. 7014 records from (Figure 6) Distribution of planktic foraminifera of ODP Hole 159-958A. 44 records from Leegmoor (Moormerland/Leer). 109 records from Planktic foraminifera abundance of Hole 37-333A. 145 records from Planktic foraminifera abundance of Hole 73-524. 13 records from Nannofossil abundance of Hole 94-607A. 81105 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1998) (AfrOBIS). 580 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 1394 records from Avifauna de la Isla de Cozumel, Quintana Roo_1. 899 records from Collection Insecta fossil - SMF. 2618 records from MAR-ECO (EurOBIS). 7 records from (Table 4) Concentrations of PCBs and MeSO2-PCBs in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 125 records from Artenbestimmung. 3 records from Planktic foraminifera abundance of Hole 54-424B. 1101 records from Colección de Entomología - Orthoptera. 18 records from Thirteen new records of ferns from Brazil. 378 records from (Figure 10) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-537. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 2413 records from Literature based species occurrence data of birds of North-East India. 27 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 12717 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 150169 records from UWFC Ichthyology Collection. 2810 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 186 records from Schulhof Goethe-Gymnasium (Emmendingen). 617 records from Planktic foraminifera abundance of Hole 23-223. 4 records from Range table from planktonic foraminifers in ODP Hole 141-862C. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 41 records from Range table from planktonic foraminifers in ODP Hole 180-1110B. 52 records from A new species of Cordyligaster Macquart, reared from caterpillars in Area de Conservacion Guanacaste, northwestern Costa Rica. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 10 records from Feuchtwiesen Wippertal bei Wippra. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 7 records from Nannofossil abundance of Hole 9-78. 93 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683B. 81 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE272. 2 records from Benthic foraminifera abundance of Hole 42-374. 56685 records from MISS_DC_01MAR2006. 463 records from Facultad de Ciencias Exactas y Naturales Universidad de Buenos Aires Coleccion BAFC de Hongos. 10 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_996. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 56 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 4943 records from Collembola Collection. 4 records from Two new species of the genus Chlopsis (Teleostei: Anguilliformes: Chlopsidae) from the Southwestern Pacific.. 54 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Ciudad Pérez (Luna & Luna, octubre 1999). 743 records from Fish monitoring data in Lake Kasumigaura. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 52 records from Total foraminifera counts from M35/1_MSN1058. 151 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1246-4. 6 records from On the Chilopoda from Turkey. 207 records from Biosphäre Bliesgau. 55345 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 44 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/580-12. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD22. 510 records from Alterra (NL) - Microarthropods inventory in a range of forests. 931045 records from Fishbase. 77 records from Empria and Monsoma in Japan. 585 records from Ascomycetes of Russian Fennoscandia. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 100 records from BIRDRACE Stuttgart 100 trööt. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 131 records from Assemblage of living benthic foraminifera in sediment core GeoB3715-1. 26 records from Plasm bearing foraminifera counts from M35/1_MSN1052. 16087 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 3 records from Blankenfelder See. 29 records from Phytoplankton abundance at station Rigel_2_2005-05 in May 2005, Chipana, Chile. 7 records from Phytoplankton abundance at station Rigel_4_2005-07 in July 2005, Chipana, Chile. 12 records from Distribution of hydropolyp species in surface sediments of the Red Sea (Table 5). 228 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 11 records from Phytoplankton abundance at station Sechin_2003-11-06_2, Casma, Peru. 94 records from Nationalpark Jasmund. 216 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 3 records from Phytoplankton abundance at station Rigel_2_2005-07 in July 2005, Chipana, Chile. 267 records from Phytoplankton abundance and species composition in the North Balearic Sea in March 2003. 2 records from MfN - Glacial erratics. 9913030 records from Dutch Vegetation Database (LVD). 15 records from Pollen profile 2 from Richland Creek. 178071 records from The Flora of County Wexford. 8 records from Nannofossil abundance of Hole 49-409. 2 records from Nannofossil abundance of Hole 66-491. 1949 records from (Table 4b) Calcareous nannofossil distribution on ODP Hole 117-721B. 2 records from Nannofossil abundance of Hole 60-459B. 1428 records from Shellfish (GNHM-MS). 32606 records from TSB Lichen Herbarium. 3569 records from Relative abundance of planktic foraminifera in sediment core GeoB2204-2. 65 records from Meiofauna abundance in sediment core 12930-007. 517 records from Inventario de los murciélagos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, Baja California, México. 6019 records from iziko South African Museum - Mollusc Collection (AfrOBIS). 5183 records from DAO Herbarium Type Specimens. 140 records from Distribution of planktic foraminifera of sediment core GIK23424-3. 84 records from Planktic foraminifera counts of sediment core V22-188. 15166 records from Insect Collection of Yokosuka City Museum. 493 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE255. 23 records from TBW-Schafberg. 437 records from Gymnospermatatophytina Collection of Saitama Museum of Natural History. 14719 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 50 records from Planktic foraminifera abundance of Hole 60-457. 877 records from Benthic foraminifera abundance of Hole 40-362. 1301 records from Collection Hymenoptera SMF. 940 records from Mastofauna de la vertiente occidental (oeste) del Parque Nacional Pico de Orizaba, Puebla (Fase 1). 21000 records from Akita Prefectural Museum:Observation Records of Birds in Akita Prefecture. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 169 records from Sediment components of core L008/23. 57 records from (Figure 5) Foraminifera abundance and sea-surface temperature of sediment core JM97-948/2A. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1222-1. 48 records from Deutsche Schule Budapest. 124 records from Birdrace-LohmannsAdleraugen-Münster. 297 records from Foraminifera abundance of Hole 60-454A. 118 records from Natur aus zweiter Hand am Muldestausee. 4 records from Occurrence of mammalia relicts at site Klausennische. 1 records from Nothrus theleproctus. 420 records from Planktic foraminifera abundance of Hole 62-466. 1592 records from Range table from planktonic foraminifers in ODP Hole 139-856A. 4 records from Range table from planktonic foraminifers in ODP Hole 178-1100D. 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 2 records from A new workerless inquiline in the Lower Attini (Hymenoptera: Formicidae), with a discussion of social parasitism in fungus-growing ants.. 868 records from (Table 3) Planktic foraminiferal abundance in Oligocene to Early Pliocene sediments of ODP Hole 177-1090D on the Agulhas Ridge, South Atlantic. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 150 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 166 records from Planktic foraminifera abundance of Hole 9-82A. 72 records from Range table from planktonic foraminifers in ODP Hole 172-1058A. 29 records from Range table from planktonic foraminifers in ODP Hole 175-1079A. 1824 records from (Fig. 5) Occurrences of selected planktonic foraminifers in samples from ODP Hole 184-1148A in the South China Sea. 829 records from Colección Ornitológica Universidad de Nariño. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 1998 records from Aves de la cuenca media del río Bogotá. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 27299 records from NCSM Vertebrate Paleontology Collection. 66 records from Total foraminifera counts from M35/1_MSN1059. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 148 records from Flora de los ecosistemas de la zona alta del río Coello. 12 records from A new North American species of Pogonomyrmex (Hymenoptera: Formicidae) from the Mohave desert of Eastern California and Western Nevada.. 1 records from A new species of Tyrannomyrmex (Hymenoptera: Formicidae: Myrmicinae) from India.. 412 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 10 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 4042 records from SMNS Palaeontological collection - Tertiary mammals. 14270 records from Natural History Museum Rotterdam (NL) - Plantae collection. 57 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 323-U1341. 3761 records from Atlas of the Amphibians and Reptiles of Poland. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 1664 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 28 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 719 records from IBF Monitoring of Plant Galls. 51933 records from CESJ - Herbário Leopoldo Krieger. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 149 records from Wirbach. 193 records from Gelände des Schulzentrums am Himmelsbarg. 132 records from Aachtobel. 101 records from (Table 4a) Downcore distribution of live benthic foraminifera of sediment core SW_3a, California continental borderland. 251821 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 21 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 289 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 76 records from Faunal assemblage of sediment core GS7603-10. 137 records from Total foraminifera counts of multinet M21/1_MSN603. 134 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Strigidae. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 53 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 185 records from Epi-endofauna abundance in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 99 records from Dalbek-Schlucht. 122 records from Nannofossil abundance of Hole 37-334. 79 records from Total foraminifera counts of multinet M12/3_MSN560. 143 records from Total foraminifera counts of multinet M21/3_MSN674. 373 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 6 records from Microzooplankton abundance and biomass at station NBP97-03-08-2. 180 records from (Table 1) Distribution of plaktonic foraminifers in ODP Hole 125-786A. 13 records from Meiobenthos investigations in the Black Sea during Poseidon cruise PO317/3. 9 records from Nannofossil abundance of Hole 1-2. 84 records from (Table 2) Distribution of nannofossils in DSDP Hole 87-583. 7 records from Nannofossil abundance of Hole 38-336. 3 records from Nannofossil abundance of Hole 51-417B. 15 records from Nannofossil abundance of Hole 11-104. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 1038 records from (Appendix 2-4) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 31-292 in the western Pacific Ocean. 32 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2157-3. 907 records from (Appendix 2-8) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 86-577 in the western Pacific Ocean. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 38 records from BB-Biodiversität a. 34 records from Abundance of coccosphere-units of sediment core GIK23071-3. 35 records from Nannofossil abundance of Hole 78-543. 28 records from Nannofossil abundance of Hole 1-3. 11377 records from EFC - Herbário Escola de Florestas Curitiba. 591 records from Planktic foraminifera counts of sediment core V16-25. 43242 records from Bentos collection of the Museum of Nature and Human Activities, Hyogo. 1932 records from Benthic and planktonic foraminifera in ODP Hole 123-766A (Table 1-4). 27543 records from Biodiversidad de la apifauna de Yucatán. 7956 records from NCOS (OBIS China). 82756 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 202 records from Diversidad y conservación del germoplasma de henequén Agave fourcroyedes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 2304 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 16933 records from Lepidoptera (Specimens NRM). 39 records from Table 3. Macrofossils of invertebrate animals. 10271 records from Planktic foraminifera counts (census) of sediment core MD96-2084. 78 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 130-807C. 4537 records from Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1674 records from (Table 3) Neogene benthic foraminifers of ODP Hole 120-751A. 91705 records from Marine and Coastal Management - Copepod Surveys (AfrOBIS). 144 records from (Table 2) Absolute abundance, diversity, and relative abundance of benthic Foraminifera species in Upper Pleistocene - Holocene bottom sediments from Core Vulk-34-90. 100958 records from UWBM Ornithology Collection. 181 records from (UTCA) University of Tennessee - Amphibians Collection. 5 records from Analyses of the recent components of sediment core PS1400-4. 31157 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2003) (AfrOBIS). 25959 records from Royal Ontario Museum: Entomology. 111905 records from Herbarium Willing. 267 records from Freshwater shellfish Specimens of Taga Town Museum, Shiga Pref., Japan. 145 records from NSG Nollig. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 5 records from Occurrence of mammalia relicts at site Erbiceni. 202194 records from Tulane University Museum of Natural History. 16 records from Radiolaria assemblage in sediment core GIK23071. 112 records from Planktic foraminifera abundance of Hole 2-12C. 1012 records from Amphibian and Reptile Conservation - NARRS Data 2007 - 2011. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 186 records from Diversity, standing stock and distribution of dead benthic foraminifera suborder groups (Table 4+6). 873 records from Caire-Chabrand Collection. 41640 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 273 records from Range table from planktonic foraminifers in ODP Hole 155-941B. 3 records from Range table from planktonic foraminifers in ODP Hole 174-1071F. 624 records from (Table 2) Distribution of benthic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 1065 records from Alterra (NL) - Microarthropods inventory in drift sands. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 138 records from Plasm bearing foraminifera counts from multinet SO119_MSN1278. 306 records from Size of planktic foraminifera at CTD station PS55/037. 51 records from Relative abundance of live benthic foraminifera of sediment core M5/2_93MC. 1794 records from Herbarium BSG Lichenes. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 21 records from (Table 2) Distribution chart of calcareous nannofossils of ODP Hole 135-834A. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2 records from Abundance of benthos infauna at station GIK23071-1. 332 records from Forster herbarium, Göttingen (GOET). 2005 records from EcoRecord - Odonata (Dragonfly and Damselfly) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 17532 records from BioFresh Pond Data. 3995 records from SMNS Palaeontological collection - Tertiary mammals. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 8518 records from Upper Silesian Museum, Bird Observations. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 238 records from Total foraminifera counts from multinet M31/3_MSN913. 25329 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1603 records from Composition of the coccolith flora in sediment core GeoB1710-3. 6659 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 19 records from (Table 4) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704B. 378 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 622 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 39 records from Stausee Weiditz. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 152 records from Plasm bearing foraminifera counts of multinet SO118_MSN1252. 9 records from Distribution of planktic foraminifera of sediment core GIK23352-3 at stadium 5.5. 9 records from Content of coarse fraction and G. menardii in sediment corev V25-65. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 85 records from Abundance of planktic foraminifera at CTD station PS55/084-1. 113 records from Abundance of calcareous dinoflagellates of sediment core GeoB1117-2. 2615 records from Collection Ornithologie - ZSRO. 46 records from (Table 1) Distribution of planktic foraminifera in sediments from Core AMK4-410GC. 279 records from Herbarium of Lars Levi Laestadius. 11 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/088-7. 1 records from Microplankton counts and carbon biomass at station TT007_10-CTD123. 16 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/090-4. 67 records from Nannofossil abundance of Hole 29-278. 1381 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 30 records from Nannofossil abundance of Hole 47-398A. 180 records from Range table from ostracoda in ODP Hole 144-871A. 8029 records from Bishop Museum Data (OBIS distribution) (USOBIS). 980 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 14 records from Occurrence of mammalia relicts at site Klithi. 8 records from Occurrence of mammalia relicts at site Oberkassel bei Bonn. 31 records from Planktic foraminifera abundance of Hole 76-534. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-20-3. 7 records from Distribution of meiobenthos in sediment core M23_199 of the northeastern Atlantic (Table 1). 1 records from Wildnis Erzental. 18 records from Nannofossil abundance of Hole 55-431. 88 records from (Table 4) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-658A. 36 records from UC Davis Department of Anthropology Museum. 7602 records from Finnish Entomological Database: Trichoptera. 9281 records from Distribution of planktic foraminifers of core V30-40. 123 records from Phytoplankton abundance in surface water during Professor Vodyanitskiy cruise PV30_1. 296 records from Planktic foraminifera abundance of Hole 67-499. 191 records from (Table 3) Distribution of principal species of benthic foraminifers in bottom sediments from Core LV28-42-5, Sea of Okhotsk. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 92 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 183 records from Schussenaue (Weingarten). 27 records from Occurrence of mammalia relicts at site Bettelküche. 127 records from Planktic foraminifera abundance of Hole 14-140. 4 records from Dinoflagellate abundance of Hole 81-554A. 12 records from Occurrence of mammalia relicts at site Luttenberg. 577 records from Planktic foraminifera abundance of Hole 84-565. 35 records from Planktic foraminifera abundance of Hole 84-566C. 3 records from Dinoflagellates, pollen and spore abundance of Hole 29-284. 25 records from (Fig. 9B) Compiled data of profile Pré-Guittard, SE France. 170 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 1741 records from Amphibian observations from Nida Valley. 79 records from Range table from benthic foraminifers in ODP Hole 172-1058B. 2 records from A new sibling species of the genus Strumigenys, with a redefinition of S. lewisi Cameron.. 12 records from Oberservation of birds at station PS14/158 along 49° West. 34603 records from Bryophyte herbarium, Göttingen (GOET). 475 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 13545 records from Collection Bryozoa SMF. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 47 records from (Table 2, 4) Distribution of benthic foraminifera and age assignments of middle to late Eocene sediments of DSDP Hole 48-401 in the Bay of Biscay. 1 records from On the Chilopoda from Turkey. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 32916 records from Insect specimen database of Atugi City Museum. 18354 records from Hokkaido University Coleoptera Collection. 9 records from Rivulus uakti sp. n. and R. amanapira sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new species from the upper Rio Negro, Brazilian Amazon.. 62 records from (Appendix H) Benthic foraminifera groups in ODP Hole 172-1055B. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 1 records from Nothrus spinifer. 1 records from Zetes fuscomaculatus. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 52819 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1573019 records from SA Flora (BDBSA). 1 records from 5. Wiener Gemeindebezirk. 3 records from Nannofossil abundance of Hole 6-48A. 50 records from Junge Heide, Radebeul/Dresden. 132 records from BIRDRACE Die Wetterauer. 77 records from Faunal assemblage of sediment core GS7603-12. 65535 records from OAC-BIO Herbarium. 94 records from Total foraminifera counts of multinet PO247/2_MSN1385. 175 records from Planktic foraminifera counts at CTD station M39/4_361CTD-18. 6 records from Microzooplankton abundance and biomass at station NBP97-03-06-8. 10 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 2421 records from Census of plant species in Toffo forest reserve. 10 records from Microzooplankton abundance and biomass at station NBP97-08-06-4. 18 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/014-4. 1 records from Planktic foraminifera counts of multinet M21/5_MSN728. 6680 records from SOMBASE PYCNOGONIDS. 234 records from Sipuncula - SMF. 3259 records from Florística de áreas protegidas en el estado de Durango. 1106 records from Planktic foraminifera abundance of Hole 21-208. 63 records from Erft in Selikum (Neuss). 202 records from Total foraminifera counts of multinet M6/7_MSN96. 102 records from Raus in die Natur. 4 records from Nannofossil abundance of Hole 6-48. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 103 records from Ostracoda abundance of Hole 24-237. 32 records from Nannofossil abundance in sediment core PS1312-4. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 117 records from Nannofossil abundance of Hole 80-549A. 17 records from Coccoliths in sediment core PS1529-8. 16 records from Diversidad de Bacterias Fotótrofas en Comunidades Microbianas Bentónicas de Bahía Concepción, B.C.S. (CIBNOR). 3 records from Nannofossil abundance of Hole 9-83A. 70 records from Birds (SMNH-BI). 7 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE236. 11220 records from (Appendix I) Planktonic foraminiferal biostratigraphy of ODP Hole 113-689B. 180 records from (Table 8) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-217. 342 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fish. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 7 records from (Table S2) Biometric data, time of ice breakup and carbon isotopic composition of adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 777 records from Planktic foraminifera counts of sediment core RC17-108. 33 records from Familientag am Schorberg. 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 118 records from Antarctic Amphipoda. 255 records from (Table 3) Occurrences of ostracodes in ODP Hole 122-763B. 1327 records from (Appendix) Abundances of benthic foraminifera in ODP Hole 105-646B. 1636 records from Flora útil del Municipio de la Huerta, Jalisco. 29 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 930 records from Megaloptera (Insecta: Neuropterida) de México. 2940 records from RSPB - Cirl bunting national surveys in the UK (SCARABBS). 29128 records from Diversidad bentónica del ambiente intermareal e infralitoral somero de Progreso, Yucatán. 4808 records from North American Sessile Marine Invertebrate Survey. 1 records from Hoplophora testudinea. 4529 records from Flora Novo Galiciana-Gramineae. 890 records from Percentages of planktonic foraminifera species in sediment core RC09-49. 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 87 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008. 10591 records from Planktic foraminifera (%) of sediment core MD97-2151. 98 records from Distribution of planktonic foraminifera in DSDP Hole 90-594 east of New Zealand. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 355 records from Culture Collection of Cryophilic Algae. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 142 records from MfN - Fossil vertebrates I. 11 records from Nannofossil abundance of Hole 11-101. 128 records from Coccoliths in sediment core PS1535-8. 20672 records from MSB Parasite Collection (Arctos). 18 records from (Table 2) Average major-element composition of glass shards from Toba Tephra Beds in Sumatra, Malaysia, India, and the Indian Ocean. 1237 records from Nematode abundance in sediments obtained during RRS Charles Darwin cruise CD179. 2911 records from Distribution of foraminifera of sediment core GeoB1112-4. 111 records from Planktic foraminifera abundance of Hole 9-79A. 27 records from Range table from planktonic foraminifers in ODP Hole 169-1036B. 132 records from tab 2. 1050 records from Relativ abundances of total live fauna of benthic foraminifera in surface sediments (Table C1.1). 661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 100193 records from Mammalogy Collection - Royal Ontario Museum. 10592 records from Wikander. 18 records from RSPB - Black grouse lek survey in Lothian and Borders, 2008 (RSPB). 1 records from Oribates mollicomus. 148 records from Faunal assemblage of sediment core GS7603-11. 1 records from Microzooplankton abundance and biomass at station TT050_4-7. 13 records from Distribution of meiobenthos in sediment core M19_238-2 of the northeastern Atlantic (Table 1). 216 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 101 records from Naturgrundstück (Eutin). 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 2014 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 112-688A. 2091 records from Estudio florístico de las gramíneas de Zacatecas. 3420 records from Nova Scotia Museum of Natural History, Halifax, NS, Canada. 21680 records from Osaka Prefectural Minoh Park Insects Museum. 494 records from Biologische Station im Kreis Wesel. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 21 records from Bach. 165 records from Total foraminifera counts from multinet M31/3_MSN898. 71 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 656 records from ZFMK Sound Archive. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 25 records from Ostracoda abundance of Hole 48-404. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 196 records from (Table 2) Distribution of planktonic foraminifera shells of different species in deposits from DSDP Hole 30-289. 5186 records from Distribución conocida y potencial de 48 especies de hongos silvestres comestibles en la región central del país. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 73 records from Nannofossil abundance of Hole 73-520. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 3800 records from (Figure 7) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-630A. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 9031 records from AIMS - LTM Nearshore Corals (OBIS Australia). 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 16 records from Occurrence of mammalia relicts at site Buchenloch. 15 records from Planktic foraminifera abundance of Hole 17-165. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 33 records from Occurrence of mammalia relicts at site Gamssulzenhöhle. 22 records from Planktic foraminifera abundance of Hole 6-48B. 1 records from Range table from planktonic foraminifers in ODP Hole 139-858F. 69907 records from CU Invertebrate Paleontology. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 517 records from Schulzentrum "Parc Hosingen". 4 records from Microzooplankton abundance and biomass at station TT054_7-18. 30 records from Nannofossil abundance of Hole 94-608. 5918 records from Catálogo y recopilación de datos científicos de los lepidópteros nocturnos de México, pertenecientes a cinco familias. 181 records from Marine Biological Association - RISC and ALERT Marine Non-Native Species (Chinese Mitten Crab, Wakame and Carpet Sea Squirt) Records. 1017 records from Broadland Environmental Services Limited - Water vole distribution within Broadland (2003-2006): based upon field signs, sightings and trapping data.. 138 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV4. 8684 records from Individual Sightings. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 218 records from Planktic foraminifera assemblage in sediment core GIK16396-1. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 258 records from Planktic foraminifera abundance of Hole 40-364. 13 records from Range table from benthic foraminifers in ODP Hole 194-1192A. 17450 records from The Scottish Ornithologists' Club - Fife breeding bird tetrad atlas 1991-99. 14522 records from MVZ Egg and Nest Collection (Arctos). 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D4. 14 records from Occurrence of mammalia relicts at site Joint Mitnor Cave. 7971 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Motacillidae. 17170 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 33 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 779 records from Guadeloupe_Ananas. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 1447 records from Odonata of the Congo River 2010 expedition. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 7 records from Planktic foraminifera counts of multinet M21/5_MSN732. 1465 records from Centro Nacional Patagonico Ichthyological Collection (OBIS South America, SOUTHERN OCEAN SUB-NODE). 17 records from (Table 2) Distribution of Manumiella seelandica in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 109266 records from Recent Invertebrates Specimens. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 94 records from FFH-Gebiet Paartal. 172 records from Total foraminifera counts of multinet PO247/2_MSN1371. 1645 records from IFO Bacteria database. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 20 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 76 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1214A. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 28385 records from Plan de vertebrados de la Patagonia. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 3082 records from dec2011. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 565 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 60 records from Range table from benthic foraminifers in ODP Hole 139-858C. 356 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 38 records from Plasm bearing foraminifera counts of multinet M21/5_MSN742. 3718 records from Benthos counted on dredged samples during Valdivia cruise VA53. 242 records from Schieferbrüche. 140 records from Distribution of late Turronian planktonic foraminifers in ODP Hole 114-700B. 792 records from Geochemistry and sedimentology on core PO200/10_28-1. 103 records from Range table from benthic foraminifers in ODP Hole 139-855C. 60 records from crocodylus. 1 records from Arthropoden aus südostalpinen Höhlen.. 114 records from RSPB - Tree sparrow recovery project â summary data, North West England, 2004-2010 (RSPB, NE, Wirral Borough Council, Cumbria Biodiversity Partnership). 976 records from (Table T2) Planktonic foraminifera abundance of ODP Site 170-1040 sediments. 362 records from Range table from benthic foraminifers in ODP Hole 149-898B. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 836 records from (Figure 4) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626D. 1272 records from (Table 2) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-706A. 1010 records from Distribución y algunos aspectos ecológicos de hongos hidnoides estipitados de México. 384824 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 58614 records from Marine and Coastal Management - Demersal Surveys (years 1986-1990) (AfrOBIS). 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 81 records from Revision of the snailfish genus Allocareproctus Pitruk & Fedorov (Teleostei: Liparidae), with descriptions of four new species from the Aleutian Islands.. 13 records from Environment Agency - Environment Agency white-clawed crayfish Survey of the River Lune Catchment 2004. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 5 records from Feuchtwiese. 80 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1361. 15 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1330. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_8-CTD102. 641 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Northwest African upwelling area. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 103 records from (Table 6b) Calcareous nannofossil distribution on ODP Hole 117-731C. 753 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 51 records from (Table 1) Total cyst counts and concentrations of dinocysts and pollen together with environmental parameters. 436 records from Larval fish at Helgoland Roads in 2005. 174 records from Birds (NHCA-BI). 655171 records from Bugbase, Lepidopterological Society. 10 records from Occurrence of mammalia relicts at site Adler Cave xx. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 10 records from Oberservation of birds at station PS14/149 along 49° West. 596 records from MISE Project Roaringwater Bay Otter Records, 2012-2014. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 23048 records from Herpetology Collection. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 559 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Meiofauna. 37986 records from rmca-albertine-rift-cichlids. 1496 records from Countryside Council for Wales - Stoneworts in Wales. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 10 records from Ökowerk Emden. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 5 records from Microzooplankton abundance and biomass at station TT050_7-9. 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 234 records from Baggerseen bei Krauchenwies. 21 records from Meiofauna abundance in sediment core 12930-018. 857 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 9 records from Microzooplankton abundance and biomass at station NBP97-03-05-6. 11 records from Distribution of meiobenthos in sediment core M19_232-2 of the northeastern Atlantic (Table 1). 110 records from Artenvielfalt und Kulturlandschaft. 40 records from Macrofauna biomass in surface sediment sampled during cruise DI226. 1534 records from PonTaurus collection. 140 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 44 records from Planktic foraminifera abundance of Hole 19-188. 1 records from Abundance of benthos infauna at station GIK23062-2. 1 records from Oribates fusifer. 26946 records from Diveboard - Scuba diving citizen science observations. 127 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 244 records from Range table from benthic foraminifers in ODP Hole 145-887C. 12 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 40 records from Flächennaturdenkmal Grubditz. 174 records from BIRDRACE Bon(n)apartemöwen. 2 records from Nannofossil abundance of Hole 9-82. 14278 records from (Table 4) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-700B. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 3015 records from Bird specimens in Gifu Prefectural Museum. 155 records from Bergbaufolgelandschaft am Muldestausee. 80 records from Planktic foraminifera abundance of Hole 49-411A. 88 records from Dinoflagellate abundance of Hole 28-274. 356 records from Amphibia Collection of Museum and Institute of Zoology PAS. 221 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 171B-1052A sediments. 1 records from Microfossil abundance of Hole 42-378. 140 records from Plant Living in Water (KIDR-PL). 10 records from Description of the females of Anapis castilla and Anapisona bordeaux (Araneae, Anapidae).. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD56. 96 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 4550 records from University of Alberta Museums, Freshwater Invertebrate Collection. 19 records from (Table 6) Pleistocene nannofossil range chart for ODP Hole 134-830A. 593 records from Mamíferos voladores laguna El Tinije. 31 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 510 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 83 records from Spechtwald. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 8 records from Abundance of radiolaria at station LV28-29-1. 1151 records from Coccolithophores in surface sediments of the Arabian Sea (TAble 1). 1360 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 1177 records from Phytoplankton abundance during Mikhail Lomonosov cruise ML47. 70 records from Korean Aquatic Vascular Plants. 323 records from Foraminifera abundance of sediment core IN68-29. 142 records from Birdrace-Alte_Socken-Cuxhaven. 5 records from (Table T5) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 680 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 1030627 records from Phanerogamic Botanical Collections (S). 10633 records from Biological Records Centre - Collembola Recording Scheme. 1284 records from Collection of Heteroptera. 172 records from Leben im Finkensteiner Moor. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 29 records from Range table from ostracoda in ODP Hole 151-911A. 9 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE233. 1 records from Mesozoa - SMF. 54 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 9674 records from Mammal collection of National Museum of Nature and Science. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D2. 9 records from Foraminifera abundance of Hole 64-477A. 420 records from Phytoplankton abundance in surface water in January 1996, Ilo, Peru. 3 records from Sarcodine counts and carbon biomass at station TT011_5-CTD64. 601 records from LBV 100 - Artenvielfalt am Rothsee. 138 records from Phytoplankton abundance at station DI182_11863#1. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 73 records from Planktic foraminifera counts of sediment core V24-28. 1 records from Schneifelkinder erkunden südliche Blumenpracht. 17 records from (Table 3) Nannofossil occurrence in the Albian of ODP Hole 101-635B. 2048 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 108-659A. 9271 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 4 records from Range table from planktonic foraminifers in ODP Hole 171-1049A. 128 records from (Table 2) Distribution of ebridians and actiniscidians in selected samples from DSDP Hole 90-591. 33 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071F. 63 records from (Fig. 9A) Compiled data of profile L´Arboudeysse, SE France. 32 records from Grundschüler erkunden Schulumgebung. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 33944 records from Aranzadi Zientzi Elkartea. 1359 records from GEO Biodiversity Day. 83 records from Visual Plants (144.41.33.158) - Private collection of Juergen Homeier. 617 records from (Table 5) Realtive abundance of planktonic foraminifera in sediment core AHF-11343. 237 records from Planktic foraminifera abundance of Hole 21-207. 569 records from Benthic foraminifera abundance of Hole 84-567A, Part 2. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 11 records from A new species of Probolomyrmex from Madagascar.. 149 records from Naturnahes Tal in Siena. 1 records from Collection Mammalia fossil SMF. 29 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 18959 records from Herbarium Specimens of Bonin and Ryukyu Islands. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 25128 records from rmca-albertine-rift-butterflies. 74 records from Schulwald Grundschule Brügge. 2 records from Nannofossil abundance of Hole 1-5A. 336 records from Planktic foraminifera counts of sediment core V19-185. 60000 records from Birds (NSMK-BI). 380 records from Stable oxygen and carbon isotope ratios of Globigerinoides obliquus of quantitative range chart of the ostracodes in the Pliocene-Pleistocene interval of ODP Hole 107-654A. 218 records from GTI MICROFUNGI OBSERVATION. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 34 records from Meiofauna abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 685 records from Planktic foraminifera abundance of Hole 4-30. 147 records from Planktic foraminifera abundance of Hole 22-217. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 1756 records from Relative abundances of middle Pleistocene benthic foraminifera in DSDP Site Site 90-594. 448 records from Biodiver
Keywords: GBIF; biodiversity; species occurrences